Are Women’s Rights Organisations (WROs) effective agents of social change? the efforts of WROs in overcoming challenges in legislative advocacy of the Violence Against Person Prohibition (VAPP) Act in Nigeria - Hammawa, Maimuna Gambo; Wan Mohd Nor, Murni; Adnan, Zatul Himmah; Ismail, Mohd. Mahadee (International Organization of Scientific Research, 2018)
Women organisations have been struggling for women’s rights but despite constitutional guarantee of political participation for groups, they are faced with many challenges that inspire the adoption of practical measures. This brings one to the question as to whether WROs have the capacity to successfully influence decision makers to bring about social change. This article examines the efforts of Women’s Rights Organisations (WROs) in over coming challenges in the legislative advocacy that led to promulgation of the Violence Against Persons Prohibition (VAPP) Act. Data were collected by way of document review and in depth interviews conducted with 10 WROs members. Findings indicate that WROs innovatively sought support from development partners to overcome financial constraints and incorporated National Assembly Administrators and key male legislators to deter further delay in the law reform. In conclusion, WROs represent key societal forces that challenged personalized rule and organisational in adequacies to instil change in the society.